Judicial Practice in Russia on Individual Labor Disputes of Professional Athletes - G. A. Popov (Теоретическая и прикладная юриспруденция)
The article provides an overview of the decisions made by the courts of general jurisdiction in individual labor disputes involving professional athletes in the period from August 01, 2020 to October 15, 2022. The author analyzes the judicial practice for the specified period, comparing it with similar statistics for the time period from January 2016 to October 2020. An attempt was made to answer the question of why, due to the arbitrability of individual labor disputes of athletes that became possible in August 2020, the number of such disputes resolved in state courts decreased slightly.